2004
DOI: 10.1097/01.ccm.0000134259.59793.b8
|View full text |Cite
|
Sign up to set email alerts
|

Induced hypothermia by central venous infusion: Saline ice slurry versus chilled saline

Abstract: Cold intravenous fluids rapidly induce hypothermia in swine with intact circulation. A two-phase (liquid plus ice) saline slurry cools more rapidly than an equal volume of cold saline at 0 degrees C. Ice-slurry could be a significant improvement over other cooling methods when rate of cooling and limited infusion volumes are important to the clinician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Prolonged maintenance (36 h) of mild hypothermia (34°C) by cardiopulmonary bypass following profound brain hypothermia (10-15°C) induced by aortic saline flush (i.e., 2°C; 20 l) supported intact neurological outcome in a dog model of cardiac arrest following prolonged hemorrhage [34]. In a recent advancement, Vanden Hoek et al demonstrated more rapid brain cooling using a two-phase, liquid plus ice, saline slurry than with an equal volume of cold saline [19]. Yet, all of these techniques necessarily invoke substantial systemic cooling along with brain cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged maintenance (36 h) of mild hypothermia (34°C) by cardiopulmonary bypass following profound brain hypothermia (10-15°C) induced by aortic saline flush (i.e., 2°C; 20 l) supported intact neurological outcome in a dog model of cardiac arrest following prolonged hemorrhage [34]. In a recent advancement, Vanden Hoek et al demonstrated more rapid brain cooling using a two-phase, liquid plus ice, saline slurry than with an equal volume of cold saline [19]. Yet, all of these techniques necessarily invoke substantial systemic cooling along with brain cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Cooling blood with intravenous catheters has gained interest because of its potential for long-term use [16,17]. Extracorporeal cooling strategies have been devised as simple veno-venous cooling or coolant infusion systems, or as sophisticated as carotid heat exchangers for independent control of brain and core temperatures [4,6,18,19]. While these approaches may be used in specialized hospitals for elective medical procedures, they have limited applicability for aiding in the recovery of neurological emergencies in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of 15 -30 ml/kg of 4 °C cold crystalloid (normal saline, Ringer solution, Hartmann solution) at an infusion rate >60 ml/h may induce the decrease of BT >1.4 °C (Kim et al, 2005;Kim et al, 2007;Kliegel et al, 2005;Kliegel et al, 2007;Virkkunen et al, 2004;Kämäräinen et al, 2008;Bernard & Rosalion, 2008;Bruel et al, 2008;Polderman et al, 2005;Vanden Hoek et al, 2004). However, additional cooling techniques are necessary for TH maintainance (Kliegel et al, 2007).…”
Section: Cooling Methodsmentioning
confidence: 99%
“…Animals experiments showed that early intra-arrest initiation of cooling resulted in significantly better neurological outcome than cooling after return of spontaneous circulation (Abella et al, 2004;Kuboyama et al, 1993). This concept was also evaluated in a few clinical studies.…”
Section: Alternative Thermoregulation Strategies In Cardiac Arrest Sumentioning
confidence: 99%
“…Increased risk of infection, coagulopathy, cardiopulmonary compromise and risks of re-warming erode the clinical utility of systemic therapeutic hypothermia, offsetting any beneficial effects on neurological function and limiting the achievable depth of induced hypothermia 1,9 . Moreover, induction of systemic hypothermia exhibits a significant and unpredictable lag time from institution of therapy to achievement of target temperature 10 . Selective hypothermia, initially investigated in the 1960s prior to the advent of effective cardiopulmonary bypass, has re-emerged as a potential solution to the logistical obstacles and systemic complications of whole body hypothermia 11 .…”
mentioning
confidence: 99%